Biosafety in the laboratories of the universities of Medical Sciences - Darien Nápoles Vega; Kenia Milagro Sebasco Rodríguez; Raúl Fernández Regalado; Tammy Fernández Romero; Humberto F. Olivera García (Universidad de Ciencias Médicas de La Habana, 2023)
Introduction: From the point of view of Biosafety, the Basic Biomedical Science laboratories are specialized and dangerous work environments where the probability of suffering damage, injury, or even death is always present. Objective: To substantiate the importance of biosafety in the Basic Biomedical Sciences laboratories of the Universities of Medical Sciences. Material and Methods: A systematic review was carried out according to the Prisma methodology in the period between April and May 2022. In addition, a critical reflective analysis of the current documentation was carried out. Searches were performed in Pubmed, Lilacs, and Google Scholar. The words or phrases "biological risk containment", "biosafety", "laboratory", and "medical sciences" were used. Results: A total of 21 articles that describe the procedures, equipment used, and infrastructure conditions to guarantee biosafety were obtained from the search. However, only 3 (three) are linked to the work of the Basic Biomedical Science laboratories in undergraduate and postgraduate training at the Universities of Medical Sciences. Conclusions: The prevention and control of risks in health institutions is of fundamental importance today, and biosafety must be rigorously implemented by the human resources of these facilities, in this particular case, the Biomedical Basic Sciences laboratories of the Universities of Medical Sciences, since these scenarios are not exempt from risks to the health of professors, technical teaching assistants, general assistants, students, the community, and the environment.